Serum cholinesterase as a new nutritional indicator for predicting weaning failure in patients - Liu, Jiaping; Shao, Tianyu; Chen, Hanwen; Ma, Chenyang; Lu, Xiaohui; Yang, Xiaoming; Song, Kang; Wang, Lu; Lei, Shu; Wang, Dafen (Frontiers in Medicine, 2023)
Aim The objective of this study is to examine the correlation between patient serum cholinesterase (SCHE) concentration and weaning failure in the context of invasive mechanical ventilation (IMV), as well as to identify predictors of ventilator weaning failure. Additionally, this study investigates the potential relationship between SCHE and nutritional risk for developing more effective weaning strategies. Method A retrospective observational study was conducted. The sample was collected from 227 patients with IMV over 48 h who underwent SBT before weaning. Relevant experimental samples and data collection were analyzed at the time of patient admission and before the initiation of the SBT. The correlation between SCHE and weaning failure was determined by multifactorial logistic regression and propensity matching scores. Results Weaning was successful in 127 patients and failed in 100 patients. Depending on the difficulty of weaning, 55 of these patients had difficulty in weaning and 45 had long-term weaning. In the crude cohort, experimental data collected on the day of SBT showed that SCHE concentrations were higher in patients with successful weaning than in those with failed weaning (4,514 u/l vs. 3,190 u/l p < 0.01). The critical value for predicting weaning failure was SCHE 3,228 u/l (p < 0.01). Ventilator weaning failure was predicted by multifactorial logistic regression analysis of SCHE, heart rate, and PaO2 before SBT, with SCHE predicting ventilator weaning failure (AUC 0.714; 95% CI 0.647–0.782) better than heart rate (AUC 0.618; 95% CI 0.545–0.690), PaO2 (AUC 0.59; 95% CI 0.515–0.664). After propensity-matched scores, SCHE remained an independent predictor of weaning failure (p = 0.05). And the SCHE concentration was strongly correlated with the patient’s weaning difficulties (p < 0.01). The Nutrition Risk in Critically Ill (NUTRIC) score was also significantly correlated with SCHE according to Spearman’s correlation analysis (p < 0.01). Conclusion Our study revealed that the patients who experienced weaning failure exhibited lower SCHE values compared to those who successfully underwent weaning. Before spontaneous breathing trial (SBT), SCHE, heart rate, and PaO2 were identified as independent predictors of weaning failure. Following propensity score matching (PSM), SCHE and heart rate remained independent predictors. Patients with SCHE levels below 3,228 u/l should undergo careful evaluation before weaning. Our findings suggest that malnutrition may be a contributing factor to weaning failure in patients.